Parametric Effect of Sodium Hydroxide and Sodium Carbonate on the Potency of a Degreaser - Olufemi, Babatope Abimbola (Journal of Science and Technology, 2016)
Experimental and statistical analysis was carried out on the comparative effect of sodium hydroxide and sodium carbonate on the potency of a laboratory produced degreaser in this work. The materials used include; octadecyl benzene sulphonic acid, sodium hydroxide, sodium carbonate, sodium metasilicate, carboxyl methyl cellulose (C.M.C), formadelhyde, perfume, colourant and distilled water. Different samples of degreaser were produced with varying composition of sodium hydroxide and sodium carbonate respectively. Statistical significance through methods like analysis of variance (ANOVA) of some parameters on various concentrations of sodium hydroxide and sodium carbonate was investigated. The effect of the varying compositions of sodium hydroxide and sodium carbonate was also determined by using a gray scale (GS) test, and also subjecting surfaces heavily stained with crude oil to determine and characterize the cleansing action of the degreaser. It was found that as the concentration of sodium hydroxide increases, the cleansing ability also increases, whereas the increase in concentration of sodium carbonate had no effect on the cleansing ability. The work would enable production of effective, useful and property controlled degreasers at moderate cost.